New Insight into the Geochemical Behavior of Alkali and Alkaline Earth Metals in a Frequently Subsampled Clay Pit Sample with and without Al-normalization - Jurković, Josip; Sijahović, Emina; Bašić, Fejzo (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2025)
Clays are fine-particle-size materials (less than 2 μm) comprised mainly of clay minerals, which are hydrated aluminum silicates with associated alkali and alkaline earth elements. The small particle size and complex porous structure result in a high specific surface area, which allows strong physical and chemical interactions with dissolved species. Metals can also be incorporated within the clay structure, which can be made of octahedral and/or tetrahedral sheets. Depending on the composition of the tetrahedral and octahedral sheets, the layer will have no charge or will have a net negative charge. If the layers are charged, this charge is balanced by interlayer cations. The recent research of metals in clays mainly focused on heavy metals, while investigations of light metals are rather rare. For the investigation of the behavior of alkali and alkaline earth metals in clay samples, 110 subsamples of cored samples were taken. The total contents of potassium (K), magnesium (Mg), calcium (Ca), sodium (Na), strontium (Sr), and barium (Ba) were determined using inductively coupled plasma-optical emission spectroscopy (ICP-OES). Descriptive statistics were conducted using maximum, minimum, average, and median values. Correlation and PCA analysiswith and without Al-normalization were calculated to determine the different behavior of metals, The contents of metals lie in the following sequence: K>Mg>Ca>Na>Ba>Sr. The highest correlation between metals was found between Mg and K (r=0.87) and Ba and Sr (r=0.65). PCA analysis revealed two subgroups: 1) K, Mg, Na. 2) Ba, Sr. After the Al normalization was applied, Ba and Sr showed the highest correlation (r=0.81). Ca did not significantly contribute to any of the PCA subgroups, suggesting a possible different source and behavior.